Numerical and Graphical Analysis of the Revan Topological Indices for Double Graph and Strong Double Graph of Alkanes - Vishu Kumar M.; Siva Kumar Pathuri; Rekkala Shruthi; Indira A. K.; Umair Khan; Shivani Sanjay Bishnani; Taseer Muhammad; Anjali Verma (Journal of Mathematics)
Numerous large graphs may be constructed from smaller ones, and graph operations are important in many graph theory applications. Here, we investigate the double and the strong double graphs as two graph-theoretical procedures. Alkanes, which simply contain hydrogen (H) and carbon (C) molecules and no additional functional groups, are the most basic and simplest hydrocarbons found in organic molecules. Topological indices come in a variety. There are several degree-based topological indices, including the Banhatti, Zagreb, Randi, and Revan indices (RI). In this paper, we compute a generic formula the first, second, and third Revan topological indices on the double graph and strong double graph of alkanes.